The role of the instrumental principle in economic explanations - Hoffmann, Nimi (Rhodes University, Faculty of Humanities, Department of Philosophy, 2009)
Economic explanations tend to view individuals as acting to satisfy their preferences, so that when given a choice between goods, individuals choose those goods which have greater utility for them "“ they choose those goods which they believe can best satisfy their preferences in the circumstances at hand. In this thesis, I investigate how utility theory works when it is used to explain behaviour. In theory, utility is a positive concept. It is intended to describe and explain an individual's behaviour without judging or justifying it. It also seems to be regarded as non-hypothetical, for it explains an individual's behaviour in terms of preferences which need not be shared by others, but may be wholly particular to her. This implies a distinctive way of approaching people's behaviour as isolated from and immune to the judgements of a community, for utility cannot be used as a common standard by which we judge an individual's behaviour as better or worse, appropriate or inappropriate. I argue that this theoretical treatment of utility is substantially different from the practice of using utility to explain behaviour. In the first place, when utility is used to explain behaviour as preference-guided, it treats this behaviour as rational action. An explanation of rational action is, however, necessarily governed by the instrumental principle. This principle is normative "“ it stipulates the correct relation between a person's means and her ends, rather than simply describing an existing relation. The principle is also non-hypothetical "“ our commitment to the principle does not rely on the possession of particular ends, but on having ends in general. The instrumental principle therefore acts as a common standard for reasoning about how to act, so that when we explain an agent's behaviour as rational action, we expect that her action will conform to standards that we all share in virtue of having ends. Thus, I contend, in order to explain the rational actions of an individual, marginal utility necessarily appeals to the judgements of a community.
Keywords: Consumer behaviour; Utility theory -- Economic aspects; Economics -- Sociological aspects; Marginal utility